Advances in global leadership. Vol. 6 - Mobley, William H.; Li, Ming; Wang, Ying (Advances in global leadership,, 2011)
Volume 6 of "Advances in Global Leadership" includes timely and impactful chapters on various concepts and processes associated with leading across cultures and other boundaries. In these times of accelerating complexity and global inter-connectedness, a deeper understanding of the multiple contextual, organizational, and individual variables and processes associated effective international leadership is ever more important. This Volume, drawing on authors from many different cultures and contexts, contributes to bridging and integrating conceptual and practitioner perspectives in pursuing this deeper understanding. Volume 6 includes chapters on: global mindset; leading innovation across cultures; virtual team leadership; leading sustainability; leader and expert selection; organizational culture across cultures and contexts; the future of corporate leadership development processes and practices; proactive leadership; and, coaching. Academics, management and leadership development professionals, consultants, coaches, leaders and would-be-leaders will be informed by the chapters in this Volume.